Issue Information. (18th August 2019) - Unknown
Abstract : The expression of p27 kip1 protein (red) repressed by AKT activation (the bottom row) in cultured mouse primordial germ cells (PGCs). The top row shows PGCs without AKT activation as a control. The green signal represents activated (the Ser473‐phosphorylated) AKT. The blue signal in the merged image (right) shows nucleus stained by DAPI.